Distributions of Fiber Mass, Air Permeability, and Filter Efficiency in Nonwoven Fabric Bag Filters. Issue 3 (27th January 2021) - Fukasawa, Tomonori; Kanaoka, Chikao; Kimura, Isao; Bao, Li; Ishigami, Toru; Fukui, Kunihiro
Abstract: The accurate determination of physical properties of filtration media is essential for predicting their performance for bag filtration use. The spatial distributions of fiber mass, air permeability, and thickness of three commercially available filtration media were evaluated and compared with the manufacturer's indicated values. The fiber mass and air permeability were distributed over a wide range, resulting in a large deviation from the indicated values. The filter efficiencies were measured for ten randomly sampled pieces from each filter, and the filter efficiency of the whole filtration media and particle emission rate were estimated. Even for filters with a fiber mass and air permeability close to the indicated values, their filter performances differed by approximately 15 %. Abstract : The spatial distributions of fiber mass and air permeability of three commercially available filtration media were evaluated and compared with the manufacturer's indicated values. The fiber mass and air permeability were distributed over a wide range, resulting in a large deviation from the indicated values. In addition, the filter efficiencies and the particle emission rate were also evaluated.